Academia popular da pessoa idosa (APPI) : usos e apropriações dos frequentadores do módulo da Praia de Camburi em Vitória/ES - Laurindo, Vinnicius Camargo de Souza (2014)
The spread of the aging phenomenon and its issues was accentuated in recent decades featuring the achievements of the elderly population as great advances made by society in this period. This research aims to analyze the uses and appropriations of the Academia Popular da Pessoa Idosa (Appi) [Popular Gym of Elderly] aiming to detect everyday practices (activities and social relations) that enhance its use as a public space, as well as practices and conflicts that undermine the use this space. To do so, tried to observe the behaviors, attitudes, and statements of many members of the Módulo da Praia de Camburi (MPC) [Camburi‟s Beach Module] belonging to the Appi program. In order to achieve the study objectives the following steps were taken: 1) literature survey related to the production of the Gyms of the Third Age; 2) literature review; 3) Going to the field; 4) semi-structured interviews with users of the program; 5) data analysis. The data identified a set of elements that attract users to MPC. The results emphasize that the MPC consists of a heterogeneous public. "Conflicts" were highlighted, specifically related to the different ways each user uses the space. The main results indicate that the variable structure and location, (through elements such as reputation of the place and lack of maintenance), technological items (elements such as use of sports equipment and observation of the landscape), sociability (elements like motion people and relationships developed from space), relations of belonging (elements such as concern with the maintenance of the MPC and the MPC as just another place to go) and autonomy (elements such as lack of consensus regarding support of a Professor of Physics and personal fulfillment for participating in decisions concerning the development of its activities in MPC) influence the uses and appropriations of the MPC. This research demonstrates the difficulty facing researchers trying to describe and interpret such a diverse reality as presented in Appi and the importance of understanding the formation of public space (physically and metaphorically) directly influences the uses and appropriations of users. Despite the difficulties presented, the research may help in understanding the meaning of this type of program to the user.